THE EFFECT OF EXPERIENTIAL MARKETING AND e-WOM ON CUSTOMER LOYALTY (CASE STUDY: D-LINOW RESTAURANT) - Wola, Marcelina Indriani; Massie, James D.D.; Saerang, Regina T. (Universitas Sam Ratulangi, 2021)
Tourism is currently an activity that directly monitors and engages the community, thus bringing various benefits to local and surrounding communities. Even tourism has extraordinary energy, which is able to make local people experience metamorphosis in various aspects. Tourism has many benefits for the community, even for the state, the benefits of tourism can be seen from various aspects / aspects, namely the benefits of tourism in terms of economic, socio-cultural, environmental and employment opportunities. D-Linow Restaurant is the one of Tourism in Tomohon. The visitors who have visited the D-Linow Restaurant tourism site usually share their experiences through social media. So that other people can also see their posts. And with the experience and posts on social media about the tourist attractions, many attracted the attention of other visitors.Â The purpose of this study was to determine whether The Effect of Experiential Marketing and e-WOM on Customer Loyalty at D-Linow Restaurant. This research uses quantitative methods. To achieve this goal, the researchers distributed questionnaires and the sample used 100 respondents. The results of this study indicate that experiential marketing and e-commerce have a significant positive effect on customer loyalty.Â Keywords: Experiential Marketing, e-WOM, Customer Loyalty